#75: Microbial Cell-free DNA Sequencing for Prediction of Culture-Negative Infection Events in Children with Cancer. (26th March 2021) - Goggin, K P; Griffen, A; Kohler, C; Allison, K J; Inaba, Y; Ahmed, A A; Hollemon, D; Brenner, A; Maron, G; Choi, J; Rubnitz, J E; Sun, Y; et al.
Abstract: Background: New culture-independent diagnostics are being investigated for diagnosis and prediction of infection. One method is microbial cell-free DNA sequencing (mcfDNA-seq), which can detect a wide range of pathogens directly from plasma. Immunocompromised children who develop febrile neutropenia (FN) without documented bloodstream infection (BSI) may have an undiagnosed bacterial infection, but identification of this subset is difficult. The percentage of episodes of FN caused by bacterial pathogens that did not grow in culture is unknown, as is the relative contribution of other specific etiologies such as viruses, fungi, immunotherapies, and immune reconstitution or graft vs. host disease. The value of mcfDNA-seq in FN patients is also unknown. As part of a larger study evaluating the ability of mcfDNA-seq to predict BSI in a cohort of pediatric patients with relapsed or refractory leukemia, we analyzed mcfDNA-seq results in a sample of cases of FN for which the definitive etiology was unknown. Methods: Eligible participants were <25 years of age and undergoing treatment for cancer. Remnant plasma from clinical testing was prospectively obtained and stored. Samples collected on the day of onset of FN (Day 0) and the day prior (Day –1) underwent mcfDNA-seq by Karius Inc. in a CLIA and CAP-accredited laboratory. Pathogen detection results were reported in molecules per microliter (MPM) of plasma. Negative control samples from study participants without impending or recent fever or infection were also obtained. Testing was batched and blinded, so results were not clinically available. Results: mcfDNA-seq results were obtained from eight episodes of FN in seven patients. Five episodes occurred in participants awaiting engraftment after HCT and three were receiving chemotherapy only. All participants receiving chemotherapy were receiving antibacterial prophylaxis with vancomycin and ciprofloxacin, antifungal prophylaxis with micafungin or voriconazole, and PJP prophylaxis with TMP-SMX or pentamidine. No HCT recipients were receiving antibacterial prophylaxis, but all received PJP prophylaxis, antifungal prophylaxis or treatment, and antiviral prophylaxis or treatment. Of 8 FN episodes, 4 (50%) had a common bacterial pathogen identified by mcfDNA-seq on Day 0 (Table 1). In 2 (50%) of these cases, the same organism was also identified on Day –1, at a lower concentration. One fungal pathogen was identified prior to and at the onset of FN. A common bacterial pathogen was identified in 3/64 (5%) control samples from the study population. Culture-negative sepsis was the final diagnosis in one episode; in this case, Streptococcus mitis, an important cause of sepsis in neutropenic patients, was identified in both Day 0 and Day –1 samples. In another episode where E. coli was identified, antibiotics were discontinued after 48 hours, but the patient was re-admitted within 24 hours for recurrent FN. Conclusions: In this sample of culture-negative FN episodes in pediatric patients with relapsed or refractory leukemia, mcfDNA-seq identified a common bacterial pathogen in 50% of cases. The same organism was identifiable on the day prior to FN in 50% of cases, suggesting that predictive testing might be feasible. More data regarding sensitivity and specificity of mcfDNA-seq to diagnose and predict FN are needed.